Nomadic Music: body demarcations of sonority in the migrant experience. Work in progress - María Paulina Soto Labbé; Luis Campos-Medina (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This paper is part of the research project “The everyday life in the emergency: territory, inhabitants and practices”, and it’s  focused  on  the  inquiry  about  the  social  uses  of  sound  and  music  by  the  Latin  American  immigrant  population  in Santiago de Chile. The aim is to describe some of the conceptual, methodological and empirical advances produced by the research team starting from three main hypothesis about the function of music and different kinds of sonority: a) first, they assist in the production of self-understandings and personal boundaries; b) second, they play a role to make conceivable the immigrant experience, and; c) third, they contribute to make comprehensible and manageable life in the new territory. We show the conceptual arguments that support the three hypotheses, the methodological reflection behind them and the empirical deployment involved in its testing.